Dual‐Band MIMO Dipole With Integrated Balun and Optimized Algorithm‐Based Decoupling Structure - Hatamian, Amir; Nourinia, Javad; Ghobadi, Changiz (International journal of RF and microwave computer-aided engineering, 2025)
This work presents a multiple‐input/multiple‐output (MIMO) antenna consisting of dipoles with integrated baluns and a parasitic element to reduce mutual coupling, which can cover two frequency bands. The configuration of the decoupling element is determined by using an optimization algorithm. The algorithm takes nine physical dimensions of the decoupling element as input and adjusts them by minimizing a cost function. One of these decision variables (DVs) is the number of decoupling element’s stairs (steps), which is a discrete parameter. In its simple form, the antenna cannot obtain proper isolation in the low‐frequency band, which has been solved by employing a decoupling structure in the middle of the antenna. The experimental results show that the antenna has impedance bandwidths of 1.95–3.50 GHz and 3.98–5.67 GHz, providing minimum isolation of 13.1 and 19.5 dB in the low‐ and high‐frequency bands, respectively. The ECC value is lower than 0.0038, and the peak gains are equal to 4.4 and 5.21 dB for the low‐ and high‐frequency bands. The main contribution of this work is the design of the decoupling element, which, considering the antenna’s characteristics, has improved the antenna’s isolation by 12.4 dB only in the center of the low‐frequency band.